SYNTHETIC ROUTES AND NATURAL SOURCES OF 2-PYRIDONE DERIVATIVES AND THEIR PHARMACOLOGICAL ACTIVITY - MISHRA, PREM SHANKAR; V, Ravichandiran; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: 2-pyridone is a well-known heterocyclic ring having significant biological and medical application. The molecular structures and various activities of 2-pyridone derivatives as well as their syntheses and natural occurrence are analyzed and reviewed, and their reactivity toward various nucleophiles is discussed. Methods: 2-pyridone derivatives, first naturally obtained and described as early as before the 19th century, have been attracting increasing attention in view of their high reactivity as building blocks for the preparation of compounds of various classes due to their selective transformations with different reagents. Much information describing the natural occurrence, synthesis and the significant biological activity of 2-pyridone compounds are scattered throughout the literature. There are short chapters dealing with the synthesis and activity of 2-pyridone derivatives. Results: After compiling the above material, the abundance of certain heterocyclic ring and nature of typical chemical transformations applied in current drug synthesis. It is likely this results from the abundance of these heterocycles in natural products such as alkaloids and various synthetic derivatives revealing different biological activity. This might suggest a classical approach to drug design where substrate analogs gain inspiration from existing natural ligands. Conclusions: The data considered in this review clearly demonstrate the high synthetic potential of 2-pyridone derivatives. Many biologically active heterocyclic compounds have been obtained based on this heterocyclic ring. This suggests that 2-pyridone can be used in the design of novel highly effective pharmaceuticals with a broad spectrum of bioresponses.